The accuracy and the safety of individualized 3D printing screws insertion templates for cervical screw insertion. Issue 1 (1st January 2016) - Deng, Ting; Jiang, Minghui; Lei, Qing; Cai, Lihong; Chen, Li
Abstract: Study design: Clinical trial for cervical screw insertion by using individualized 3-dimensional (3D) printing screw insertion templates device. Objective: The objective of this study is to evaluate the safety and accuracy of the individualized 3D printing screw insertion template in the cervical spine. Materials and methods: Ten patients who underwent posterior cervical fusion surgery with cervical pedicle screws, laminar screws or lateral mass screws between December 2014 and December 2015 were involved in this study. The patients were examined by CT scan before operation. The individualized 3D printing templates were made with photosensitive resin by a 3D printing system to ensure the screw shafts entered the vertebral body without breaking the pedicle or lamina cortex. The templates were sterilized by a plasma sterilizer and used during the operation. The accuracy and the safety of the templates were evaluated by CT scans at the screw insertion levels after operation. Results: The accuracy of this patient-specific template technique was demonstrated. Only one screw axis greatly deviated from the planned track and breached the cortex of the pedicle because the template was split by rough handling and then we inserted the screws under the fluoroscopy. The remaining screws were inserted in the track as preoperative design and the screw axis deviated by less than 2 mm. Vascular or neurologic complications or injuries did not happen. And no infection, broken nails, fracture of bone structure, or screw pullout occurred. Conclusion: This study verified the safety and the accuracy of the individualized 3D printing screw insertion templates in the cervical spine as a kind of intraoperative screw navigation. This individualized 3D printing screw insertion template was user-friendly, moderate cost, and enabled a radiation-free cervical screw insertion.